Community acquired respiratory virus infections in cancer patients—Guideline on diagnosis and management by the Infectious Diseases Working Party of the German Society for haematology and Medical Oncology. (November 2016) - von Lilienfeld-Toal, Marie; Berger, Annemarie; Christopeit, Maximilian; Hentrich, Marcus; Heussel, Claus Peter; Kalkreuth, Jana; Klein, Michael; Kochanek, Matthias; Penack, Olaf; Hauf, Elke; Rieger, Christina; Silling, Gerda; et al.
Abstract: Background: Community acquired viruses (CRVs) may cause severe disease in cancer patients. Thus, efforts should be made to diagnose CRV rapidly and manage CRV infections accordingly. Methods: A panel of 18 clinicians from the Infectious Diseases Working Party of the German Society for Haematology and Medical Oncology have convened to assess the available literature and provide recommendations on the management of CRV infections including influenza, respiratory syncytial virus, parainfluenza virus, human metapneumovirus and adenovirus. Results: CRV infections in cancer patients may lead to pneumonia in approximately 30% of the cases, with an associated mortality of around 25%. For diagnosis of a CRV infection, combined nasal/throat swabs or washes/aspirates give the best results and nucleic acid amplification based-techniques (NAT) should be used to detect the pathogen. Hand hygiene, contact isolation and face masks have been shown to be of benefit as general infection management. Causal treatment can be given for influenza, using a neuraminidase inhibitor, and respiratory syncytial virus, using ribavirin in addition to intravenous immunoglobulins. Ribavirin has also been used to treat parainfluenza virus and human metapneumovirus, but data are inconclusive in this setting. Cidofovir is used to treat adenovirus pneumonitis. Conclusions: CRV infections may pose a vital threat to patients with underlying malignancy. This guideline provides information on diagnosis and treatment to improve the outcome. Highlights: Community acquired viral respiratory tract infections can be life-threatening in cancer patients. Respiratory virus infections need early and appropriate management to improve outcome and avoid outbreaks. This guideline summarises recommendations by the AGIHO on community acquired respiratory viruses in cancer patients.